PELAYANAN PUBLIK BERBASIS E-GOVERMENT DALAM APLIKASI E-PUSLUH DI BIDANG PENYULUHAN KOTA PALU - Rini Oktavianti; Nawawi Natsir; Nuraisyah Nuraisyah (CV. ALIM'SPUBLISHING, 2024)
The aim of this research is to find out how e-Government based public services are and to find out various factors inhibiting services in the e-Pusluh application in the Extension Sector of Palu City. The location of this research includes the Palu City Food Security Service. The types of data used are primary data and secondary data. The technique for collecting data and information is in-depth interview observation using interview guides and documentation. Determining informants was carried out using purposive sampling. The number of informants in this research was 05 (five) people. The data collected is filtered and selected based on needs which are then analyzed using qualitative descriptive methods.The theory used fromHarvard JFK School of Government, to implement the concept of digital-based public services, there are three elements of success that must be owned and taken seriously, namely Support, Capacity, and Value. Based on the research results, it was found that the implementation of E-Government based public services in the e-pusluh application in the Extension Sector of Palu City. Support or support from government leaders in the form of presidential regulations regarding the implementation of electronic-based government systems, regulations regarding the implementation of E-Government in general in Sulawesi Province Center and socialization of e-pusluh. Capacity or empowerment from the availability of information technology infrastructure resources such as computers, printing and WiFi is sufficient as well as the availability of competent human resources in carrying out e-government based services. The value element is the benefit felt by the Palu City Food Security Service instructors, namely providing convenience for both officers and instructors in reporting agricultural extension activities. The benefits felt by instructors include saving time without having to queue, online services can also save costs and transportation. The inhibiting factor for services in the e-Pusluh application is the lack of socialization from the Palu city government which is felt by the instructors, making many instructors still not understand how to use the e-Pusluh application. This is an obstacle in the process of implementing the e-pusluh application. Apart from that, the obstacles faced are the lack of familiarity of instructors, especially the elderly, with existing technologies and frequent maintenance on the e-pusluh application.